Bifurcation Analysis for a Free Boundary Problem Modeling Growth of Solid Tumor with Inhibitors (Communications in Mathematical Research, 2020)
This paper is concerned with the bifurcation analysis for a free boundary problem modeling the growth of solid tumor with inhibitors. In this problem, surface tension coefficient plays the role of bifurcation parameter, it is proved that there exists a sequence of the nonradially stationary solutions bifurcate from the radially symmetric stationary solutions. Our results indicate that the tumor grown in vivo may have various shapes. In particular, a tumor with an inhibitor is associated with the growth of protrusions.